GAYA KEPEMIMPINAN DAN MOTIVASI, PENGARUHNYA TERHADAP KINERJA PEGAWAI - Tia Wahyu Saputri (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine whether leadership style and motivation affect the performance of Bank BTPN Padang City employees. The type of research used is quantitative research. Data was collected by distributing questionnaires to 32 respondents from Bank BTPN Padang City employees. This research uses multiple linear regression analysis method. The results of this study indicate that, based on the t statistic test, the t value for the leadership style variable is 3.233 > t table 1.695 and the significant value is 0.002 < 0.05. While the motivation variable is 5.637> t table is 1.695 and the significant value is 0.000 <0.05. So it can be concluded that leadership style and motivation have a significant effect on employee performance.